Studies on supercapacitor electrode performance of novel (AlCuCoFeMnNi)3O4 high entropy spinel oxide admixed with different carbon-based additives - Gupta A.K.; Kumar A.; Marndi M.; Giri N.K.; Shahi R.R. (My University, 2025)
The present investigation aims to synthesize a novel (AlCuCoFeMnNi)3O4 type high entropy spinel oxide through the sol-gel and investigate the effect of different carbon-based additives on charge storage performance. The formation of the inverse spinel phase of [B(AB)O4] type inverse spinel phase was confirmed through the detailed x-ray diffraction analysis of the synthesized sample. The synthesized spinel phase was indexed with the space group of Fd−3m and has a lattice parameter of 8.2697 Å. The synthesized high entropy oxide (HEO) phase Ni, Co, and Fe coexists in +2 and +3 states. At the same time, Cu in +2 state, Al in +3 state, and Mn in +3 and +4 states confirmed through x-ray photoelectron spectroscopy. The electrochemical charge storage performance of synthesized HEO was measured through the three-electrode setup in 2 M KOH aqueous electrolyte solution in two different potential windows, such as −0.2 to 0.4 V and 0.0 to 0.5 V. Different carbon-based conducting materials such as acetylene black, reduced graphene oxide (RGO), and carbon particles obtained from 10-hour ball-milling of used dry cell carbon electrode (CP). The charge storage mechanism changes from electrochemical double layer capacitance to pseudocapacitive type as the potential window varies from −0.2 to 0.4 to 0 to 0.5 V. The value of specific capacitance for an electrode made of HEO with acetylene black, RGO, and CP was found to be 32.67, 7.50, and 4.58 F/g and 30.68, 16.33, and 9.05 F/g in the potential window of −0.2 to 0.4 V and 0 to 0.5 V at a scan rate of 5 mV/s, respectively. The cyclic performance of the developed three electrodes was measured at a scan rate of 100 mV/s for 1000 cycles, and it was found to be 94%, 98%, and 99% for electrodes made of HEO with acetylene black, RGO, and CP, respectively. © 2024 John Wiley & Sons Ltd.